Formación académica en la educación superior de Posgrado en el área administrativa. Diseño de un programa de especialización para la Universidad Técnica de Cotopaxi. Mención Gestión de la Información - Zambrano Estrella, Martha Francisca (2015)
This research refers to a feasible project of transcendence in education and in the administrative field, to the staff training who works at the secretarial field in universities Zone No 3 of the country and graduate students from career of the Secretarial Executive Management of the Cotopaxi Technical University. The main categories to be discussed are: Superior Education, Document Management, Systems and Processes, Feasibility Analysis based on the Bibliographic and field research, to generate a proposal for intervention. The pattern we are going to work is Secretariats of five universities from the region No 3 in the country. The general objective of this research is to determine the educational requirements of Secretaries. The general objectives pursued are: To establish the training needs in Information Management from professionals of different careers, graduates of third level, who works like Secretaries, to contribute to the specialized training at graduate level of professionals who work as secretaries in five universities, by creating a specialization program in INFORMATION MANAGEMENT at the Technical University of Cotopaxi. The specialization in Information Management would be the beneficiaries the professionals who works like Secretaries.